ESCITALOPRAM IN THE TREATMENT OF OBSESSIVE-COMPULSIVE DISORDER: A DOUBLE BLIND PLACEBO CONTROL TRIAL - Khan, M. Nasar Sayeed; Hotiana, Usman Amin; Ahmad, Salman (Journal of Ayub Medical College Abbottabad, 2007)
Background: The tolerability and efficacy for patients with obsessive-compulsive disorder (OCD) in a large, sample on Escitalopram was studied. Methods: A total of 100 adults with a confirmed diagnosis of OCD were included. The percentage of patients with an adequate drug trial, defined as 42 days of continuous treatment with a serotonin- reuptake inhibitor or placebo at dosages at or above established minimal effective dosages. Results: Ninety-six percent of the adults who were newly diagnosed with OCD in the index year had an adequate trial of medication after their first visit for OCD. By the second half of 42 days the patient who were responding to the treatment were randomly allocated to two groups. One group received the same drug and other group was given placebo. The results were complied at the end of three months of each patient treatment. No additional psychotherapy was offered to these patients during this time period. Conclusions: Despite the typically chronic course of OCD, many patients with OCD responded to the Esciatolpram at the dosage of twenty milligram per day. Key words: Esciatolpram, Obsessive Compulsive Disorder (OCD)